Science and Technology of Liberation in Latin America: conceptual bases and normative principles - Pallitto, Nahuel; Juarez Rusjan, Nazareth; Molina, Iriel Surai; Folguera, Guillermo (SCT Proceedings in Interdisciplinary Insights and Innovations, 2024)
In this work the categories and principles of Enrique Dussel’s Ethics of Liberation were presented with the objective of outlining the conceptual bases of a Science and Technology of Liberation in Latin America.(1,2,3,4,5) Scientific knowledge and technological tools can serve as an instrument of domination or can, on the contrary, contribute to liberation. To promote the latter, the work offered normative principles that allow us to judge and orient the natural sciences and their technological developments in our region. These principles contain a material aspect linked to the affirmation of the life of communities denied by a dominant world-system, a formal aspect that points to the need for their participation in the establishment of research agendas and technological developments, and a feasibility aspect that recognizes the conditions for the concrete realization of the remaining principles.(6,7,8) To illustrate all this, Agroecology was presented as a possible expression of and opportunity for a Science and Technology of Liberation in favor of the oppressed. The final reflections highlighted the importance of considering the world of the systemic victims as the point of departure and arrival of all scientific-technological research with pretensions of ethical goodness